FCGBP functions as a tumor suppressor gene in head and neck squamous cell carcinoma - Lijuan Zeng; Jun Zeng; Jianfeng He; Yongqi Li; Chengwei Li; Zhiyan Lin; Guangwei Chen; Huilin Wu; Libin Zhou (Discover Oncology)
Abstract Purpose The pathogenesis of head and neck squamous cell carcinoma (HNSCC) was complex and the overall survival was not satisfying. It was urgent to uncover novel molecules that play vital role in HNSCC for disease monitoring and drug development. Methods Distinguished expression of FCGBP mRNA in HNSCC was analyzed by TCGA-HNSC and three GEO datasets, the relationship between FCGBP and clinical stage and survival was analyzed by GEPIA 2, the immune infiltration pattern analysis was conducted by TIMER 2.0, pathways affected by FCGBP was conducted by GSEA and GO/KEGG. In vitro experiments (including qRT-PCR, siRNA transfection, CCK8, transwell assay and flow cytometry) were conducted to confirm bioinformatic analysis. Results FCGBP was down-regulated in tumor samples compared with normal tissues at both mRNA and protein levels, and positively correlated with survival in HNSCC. Genes co-expressed with FCGBP were mainly enriched in immune-related biological processes and pathways. GSEA indicated that FCGBP was associated with activated immune reaction and inhibiting well-known pro-tumor pathways. GSE41613 validated FCGBP as an independent prognostic marker for HNSCC and FCGBP was down-regulated in HNSCC cell lines by qRT-PCR. Migration and invasion of SCC9 and CAL27 were enhanced by FCGBP-targeting siRNAs, the ratio of cytotoxic T lymphocytes were down-regulated while the ratio of myeloid-derived suppressor cells were increased by FCGBP-targeting siRNAs. Conclusion FCGBP was a tumor suppressor gene and was an independent prognostic marker for better survival. The underlying mechanism may be that FCGBP inhibited tumor migration and invasion and activated immune response against tumor cells.